2012
DOI: 10.1038/cr.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 promotes caveolin-dependent degradation of TGF-β type I receptor

Abstract: Protein that interacts with C kinase 1 (PICK1) is a critical mediator of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) trafficking in neural synapses. However, its ubiquitous expression suggests that it may have other non-neural functions. Here we show that PICK1 antagonizes transforming growth factor beta (TGF-β) signaling by targeting TGF-β type I receptor (TβRI) for degradation. Biochemical analyses reveal that PICK1 directly interacts with the C-terminus of TβRI via its PDZ domain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 54 publications
2
56
2
Order By: Relevance
“…38 Furthermore, PICK1 was recently reported to increase caveolin-dependent endocytosis of TβRI, which promotes its degradation, and its effect was abolished by inhibition of autophagy. 27 Here, we uncovered a direct interaction between Sirt7 and PICK1, and we demonstrated that PICK1 knockdown rescues the effect of Sirt7 depletion on the reduction of TβRI. In Figure 7E and 7G, PICK1 was decreased by autophagy activator or Sirt7 siRNA, but it was increased by autophagy inhibitor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…38 Furthermore, PICK1 was recently reported to increase caveolin-dependent endocytosis of TβRI, which promotes its degradation, and its effect was abolished by inhibition of autophagy. 27 Here, we uncovered a direct interaction between Sirt7 and PICK1, and we demonstrated that PICK1 knockdown rescues the effect of Sirt7 depletion on the reduction of TβRI. In Figure 7E and 7G, PICK1 was decreased by autophagy activator or Sirt7 siRNA, but it was increased by autophagy inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…We focused on protein interacting with protein kinase-Cα (PICK1) because it has been shown to interact with TβRI and to increase TβRI degradation, and its effect was abolished by inhibition of autophagy. 27 In cardiac fibroblasts, the PICK1 protein level decreased by Sirt7 knockdown and by autophagy activator, whereas its level increased by autophagy inhibitor (Figure 7E and 7G). These results indicate that the PICK1 level changes in parallel with TβRI, depending on the status of autophagy.…”
Section: Sirt7 Maintains Tβri Protein By Interacting With Protein Intmentioning
confidence: 99%
“…43 Very recently it was shown that PICK, a critical mediator of AMPAR trafficking in neuronal synapses, is overexpressed in breast cancer and antagonizes TGF-β1 signaling by promoting caveolin-dependent degradation of TβRI, thus abolishing TGF-β1-induced growth inhibition. 44,45 However, it was also reported that TβRI is a target of homeoprotein Six1 and Six1-induced upregulation of TβRI is required to switch of TGF-βI signaling to the prometastatic phenotype, such as EMT. 46 Although our study reveals that modulation of either TβRI or TβRII by PPARδ-ABCA1-Cav1 signaling provokes similar effect in prostate carcinoma cells, further studies are required to clarify whether TβRI and TβRII have differential functions in the shift of TGF-βI signaling depending on cellular context and origins.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolae-mediated endocytosis has been shown to negatively regulate TGF-β signaling by promoting TGF-β receptor turnover, probably via Smad7/Smurf-catalyzed ubiquitination [8,39]. The existence of caveolin-1 in early endosomes led us to ask whether caveolin-1-positive early endosomes participate in TβRI degradation.…”
Section: Detection Of Sara Rab11 and Smad7/smurf2 In Caveolin-1-posimentioning
confidence: 99%